PET and PET/CT : a clinical guide - Alavi, Abass; Lin, Eugene (Thieme, 2009)
Presenting oncological and nononcological applications for PET and PET/CT for a full range of clinical scenarios, this book features chapters on PET/CT for pediatric patients; the use of FDG PET in the evaluation of infection and inflammation; and, the role of PET and PET/CT in radiation therapy planning.